Studi Kasus Ibu Melakukan Kunjungan Ulang Pada Balita Pneumonia Di Wilayah Kerja Puskesmas Landasan Ulin Kalimantan Selatan - Eka Handayani; Septi Anggraeni (Jurnal Kesehatan Indonesia, 2019)
Acute respiratory infections affect many children, both in developing countries and in developed countries. acute respiratory infections that affect death and often affect children under 5 years of age, namely pneumonia. Pneumonia is the main killer of toddlers in the world with a higher prevalence compared to AIDS, malaria and measles. Every year, it is estimated that more than 2 million children under five die from Pneumonia (1 toddler / 20 seconds) from 9 million total deaths of children under five in the world. In Indonesia, pneumonia is still a big problem considering the mortality rate from this disease is still high.. Knowing the mother's case studies do repeat visits in infants pneumonia in health center Landasan Ulin. A qualitative study through interviews and documentation to one health worker. Not all mothers bring their babies repeated visit only 30% of mothers who commit repeated visit of all children under five suffering from pneumonia. Mother toddler who do repeat visits by 35% means that more mothers who do not do repeat visits by 65% this is because there are several reasons mothers do not bring toddlers pneumonia to re-visit them her son had recovered and did not cough again, there also reasoned mothers are busy.